IMPLEMENTASI KEBIJAKAN PENGEMBANGAN USAHATANI KAKAO (STUDI KASUS PT.MARS DESA TAROBOK KECAMATAN BAEBUNTA KABUPATEN LUWU UTARA) - Thalib Ruslan; Ratnawati Tahir; Akbar Akbar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The research objective is to identify policies related to the development of cocoa farming by PT. Mars and examine the implementation of cocoa farming development policies at PT. Mars. The technique of determining informants by purposive sampling. There were 10 informants, including the Head of the Agriculture Service, 1 person from the Baebunta District BPP, 1 person from the Field Coordinator of PT Mars, 6 cocoa farmers, and 1 member of the DPRD of North Luwu Regency. Technical analysis of data using qualitative analysis. The research results show that the policies made by the government and implemented by PT. Mars is, (1) conducting certification assistance, cocoa field schools, providing seeds to cocoa farmers, demonstration gardens, wet seed premiums, fertilizer assistance to farmers, (2) Implementation of policies made by the Government and implemented by PT. Mars, (3), The policies implemented by PT. Mars has had a significant impact on the growth of cocoa production and the income of cocoa farmers.